Traversing Antepartum Wernicke’s Encephalopathy: In-Depth Insights and Strategies - Joseph, Manju (Indian Journal of Nursing Sciences, 2024)
Antepartum Wernicke’s encephalopathy (WE) is a severe neurological disorder caused by a deficiency of thiamine (Vitamin B1), essential for glucose metabolism, and neuronal function. This review aims to provide an in-depth analysis of WE during pregnancy, highlighting its pathophysiology, risk factors, clinical presentation, diagnostic challenges, and management strategies. Thiamine is critical in the Krebs cycle and neurotransmitter production, and its deficiency leads to substantial biochemical disruptions and neuronal damage. Pregnant women are particularly susceptible due to their increased nutritional demands to support fetal growth and maternal metabolic changes, making them prone to thiamine deficiency and its severe neurological consequences. The clinical manifestations of WE include ophthalmoplegia, ataxia, confusion or altered mental state, peripheral neuropathy, and cardiovascular issues. Diagnosing WE during pregnancy is challenging due to its atypical presentation, requiring a high degree of clinical suspicion and awareness of risk factors. Diagnostic limitations include variable clinical symptoms and challenges in interpreting serum thiamine levels and neuroimaging findings. While neuroimaging can show characteristic brain lesions, its utility is limited by variability. Managing WE during pregnancy requires prompt recognition, immediate thiamine supplementation, continued supportive measures, and careful monitoring. Severe or refractory cases may require advanced management strategies. Pharmacological treatments include standardized thiamine administration protocols, guided by clinical guidelines and recommendations. Early detection and management of WE in pregnant women are vital to prevent irreversible neurological damage and improve maternal and fetal outcomes. Adherence to clinical guidelines is crucial to mitigate the impact of this condition.